The Effects of Direction and Velocity of Movement, and Intra-Articular Fluid Volume on Intra-Articular Pressue - Straface, S. F.; Newbold, P. J.; Nade, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
levels. In joints with simulated acute effusion the effect of position on IAP was dependent upon the volume of fluid in the joint. The results indicate that dynamic pressure levels in the moving knee are related to the movements of the joint. The characteristic and reproducible patterns of pressure may reflect changes in the structural configuration of the joint capsule and surrounding tissues during movement, and are influenced by the amount of fluid in the joint.
Keywords: Intra-articular pressure; Joint movement; Joint physiology